P2Y2 Nucleotide Receptor Prompts Human Cardiac Progenitor Cell Activation by Modulating Hippo Signaling. Issue 11 (10th November 2017) - Khalafalla, Farid G.; Greene, Steven; Khan, Hashim; Ilves, Kelli; Monsanto, Megan M.; Alvarez, Roberto; Chavarria, Monica; Nguyen, Jonathan; Norman, Benjamin; Dembitsky, Walter P.; Sussman, Mark A.
Abstract : Rationale: : Autologous stem cell therapy using human c-Kit + cardiac progenitor cells (hCPCs) is a promising therapeutic approach for treatment of heart failure (HF). However, hCPCs derived from aged patients with HF with genetic predispositions and comorbidities of chronic diseases exhibit poor proliferative and migratory capabilities, which impair overall reparative potential for injured myocardium. Therefore, empowering functionally compromised hCPCs with proregenerative molecules ex vivo is crucial for improving the therapeutic outcome in patients with HF. Objective: : To improve hCPC proliferation and migration responses that are critical for regeneration by targeting proregenerative P2Y2 nucleotide receptor (P2Y2 R) activated by extracellular ATP and UTP molecules released following injury/stress. Methods and Results: : c-Kit + hCPCs were isolated from cardiac tissue of patients with HF undergoing left ventricular assist device implantation surgery. Correlations between P2 nucleotide receptor expression and hCPC growth kinetics revealed downregulation of select P2 receptors, including P2Y2 R, in slow-growing hCPCs compared with fast growers. hCPC proliferation and migration significantly improved by overexpressing or stimulating P2Y2 R. Mechanistically, P2Y2 R-induced proliferation and migration were dependent on activation of YAP (yes-associated protein)—the downstream effector of Hippo signaling pathway. Conclusions: : Proliferation and migration of functionally impaired hCPCs are enhanced by P2Y2 R-mediated YAP activation, revealing a novel link between extracellular nucleotides released during injury/stress and Hippo signaling—a central regulator of cardiac regeneration. Functional correlations exist between hCPC phenotypic properties and P2 purinergic receptor expression. Lack of P2Y2 R and other crucial purinergic stress detectors could compromise hCPC responsiveness to presence of extracellular stress signals. These findings set the stage for subsequent studies to assess purinergic signaling modulation as a potential strategy to improve therapeutic outcome for use of hCPCs in patients with HF. Abstract : Supplemental Digital Content is available in the text.